CLINICAL-DIAGNOSTIC SPECIFICITY OF THE COURSE OF CORONAVIRUS INFECTION IN PATIENTS VACCINATED AGAINST COVID-19 (American Journal of Research in Humanities and Social Sciences, 2024)
COVID-19 is a physical illness associated with the outbreak of a coronavirus known as the Wuhan Denovirus in Wuhan in December 2019. This virus is also called SARS-CoV-2. In the world, the disease of COVID-19 has created great problems in the field of security and public health, and its clinical and diagnostic methods have become very important.